The effects of exercise on intracellular Ca2+homeostasis, Ca2+-regulating gene expression and mitogen-induced cell proliferation of murine splenic lymphocytes - Liu, Renyi; Justus Liebig University Giessen (My University, 2013)
Moderate intensity exercise improves immune functions, whereas excessive exercise has been shown to impair the immune response. The effect of exercise on immunity is mediated via numerous factors, but the exact molecular basis still isn t clear. Intracellular Ca2+ is a final focus of cellular signaling transduction, and many Ca2+-regulating factors control intracellular Ca2+ transients. Thus, this research focused on the change in intracellular Ca2+ concentration and sought to investigate whether or not exercise could affect intracellular Ca2+ homeostasis, Ca2+-regulating gene expression and mitogens-induced cell proliferation in murine splenic lymphocytes in order to uncover the potential mechanism by which exercise influences immune functions. In this study, lymphocytes were isolated from spleens. Intracellular Ca2+ was determined from Fura-2(AM)-loaded cell suspensions by using a fluorescence spectrometer. The combination of flow cytometry and CFSE-labeling techniques was used for the determination of cell proliferation. The expressions of Ca2+-regulating genes were determined by qPCR analysis. Compared with the control group, basal [Ca2+]i was significantly elevated (P<0.001, n=62) and chronic voluntary exercise significantly elevated PHA-induced [Ca2+]i in Ca2+ buffer (P<0.05, n=5); either in Ca2+ containing buffer or in Ca2+ free PBS solution, Con A or OKT3-induced change of [Ca2+]i was significantly higher in the chronic exercise group than in the control group (P<0.05,n=5); CD3+ T cells from the chronic exercise group showed higher mitogen-induced cell proliferation levels than from the control group (P<0.05,n=5). However, the expression of Ca2+-regulating genes, STIM1, ORAI1,ORAI2, Cav1.2, Cav2.3,IP3R2,TRPV4,TRPM1,TRPM5,TRPC1,MCU, P2X7,and P2Y14 were significantly downregulated (P<0.05,n=5). Acute exercise elevated basal [Ca2+]i and Con A or OKT-induced [Ca2+]i and Mn2+ influx, and reduced mitogens-induced cell proliferation in splenic lymphocytes at the 3rd hour after exercise (P<0.05,n=5). Compared with the non-exercise group, PMCA, SERCA, P2X7, and TRPC1 genes expressions were significantly downregulated (P<0.05,n=5), IP3R2 expression was significantly upregulated at the 3rd hour after exercise (P<0.01,n=5). This study suggested that chronic voluntary exercise enhanced the sensitivity of mitogens or OKT3-evoked transmembrane Ca2+ influx in murine splenic lymphocytes, i.e. high intracellular Ca2+ transients with low Ca2+-regulating gene expression; this enhanced Ca2+ was followed by enhanced cellular functions; the downregulation of Ca2+ homeostasis-related factors expression might be served as a self-protective mechanism against elevated intracellular Ca2+ signals. Secondly, a single bout of endurance exercise with high intensity might cause delayed intracellular Ca2+ upburst and impairment of cellular function in murine splenic lymphocytes. The enhanced calcium aren´t turned into an enhanced proliferation could mean exercise-induced the production of free radical serve as an obstructionmechanism of intracellular signal transduction.
Einfluss körperlicher Betätigung auf die intrazelluläre Ca2+-Homöostase, die Ca2+-regulierende Gen-Expression und die mitogen-aktivierte Zellproliferation von Milzlymphozyten der Maus
Keywords: exercise immunology; Fura-2(AM); calcium homeostasis; proliferation; calcium channels; ddc:796